How do you simplify (4x y ) ( 3x ^ { 2} y ^ { 3} ) ( - 2x ^ { 3} y )?

1 Answer
Jun 23, 2017

-24x^6y^5

Explanation:

(4xy)(3x^2y^3)(-2x^3y)
Note that all of this is just multiply.
So, you can see this as
4*x*y*3*x^2*y^3*(-2)*x^3*y
Now arrange it in your mind
Put all number together
Put all x together
Put all y together.
4*3*(-2)*x*x^2*x^3*y*y^3*y
Let's do this in different part.
4*3*-2=-24

x*x^2*x^3=x^(1+2+3)=x^6

y*y^3*y=y^(1+3+1)=y^5

So,
4*3*(-2)*x*x^2*x^3*y*y^3*y
=-24*x^6*y^5
=-24x^6y^5

Hope this help!!!